Identifikasi Sifat Fisik dan Biokimia Isolat Bakteri Asam Laktat dari Minuman Kesehatan Teratai Salju (Saussuera involucrate) - N.M.I.H. Arihantana; A.S. Duniaji; N.N. Puspawati; M.S.P. Mahardika (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2022)
Snow lotus is a 72-hour fermented health drink from a palm sugar solution with snow lotus (Saussuera involucrate) without using other additives. Fermentation of snow lotus into lactic enzymes and active lactic acid bacteria is to help maintain the body in prime condition, establish and strengthen the immune system and is beneficial for overall health. Based on previous research, 33 isolates of lactic acid bacteria had been isolated from snow lotus health drink. From the isolates that had been successfully isolated, potential for lactic acid bacteria has no known properties as a probiotic candidate. Therefore research is necessary to obtain lactic acid bacteria isolates from snow lotus health drinks which are potential as probiotic isolates. The purpose of this study was to identify the physiological properties of the snow lotus health drink which included gram staining, observation of the shape of the colonies and cell shapes, and catalase testing and also to identify the biochemical properties which included growth at a variety of different temperatures, growth ability at low pH, growth on media containing salt or NaCl, production of CO2 from glucose, and production of dextran from sucrose. Based on the physiological properties, results showed that all 33 LAB isolates from the snow lotus health drink had negative catalase properties, positive gram staining in the form of single and chain rods, and also in the form of coccus, where 13 isolates were coccus and 20 were rod-shaped isolates. Based on the biochemical properties, from the 33 isolates, almost all LAB isolates were able to grow at temperatures of 10°C, 25°C, 37°C, 45°C, pH 2, 4, 6, and media containing salt concentrations of 4% and 6.5 %, 19 isolates were able to produce CO2 from glucose, and 15 isolates were able to produce dextran from sucrose.